Multiscale variation in drought controlled historical forest fire activity in the boreal forests of eastern Fennoscandia - Aakala, Tuomas; Pasanen, Leena; Helama, Samuli; Vakkari, Ville; Drobyshev, Igor; Seppä, Heikki; Kuuluvainen, Timo; Stivrins, Normunds; Wallenius, Tuomo; Vasander, Harri; Holmström, Lasse (Ecological Monographs)
Forest fires are a key disturbance in boreal forests, and characteristics of fire regimes are among the most important factors explaining the variation in forest structure and species composition. The occurrence of fire is connected with climate, but earlier, mostly local scale studies in the northern European boreal forests have provided little insight into fire-climate relationship before the modern fire suppression period. Here, we compiled annually resolved fire history, temperature and precipitation reconstructions from eastern Fennoscandia from the mid-16th century to the end of the 19th century, a period of strong human influence on fires. We used synchrony of fires over the network of 25 fire history reconstructions as a measure of climatic forcing on fires. We examined the relationship between fire occurrence and climate (summer temperature, precipitation, and a drought index summarizing the influence of variability in temperature and precipitation) across temporal scales, using a scale space multiresolution correlation approach and Bayesian inference that accounts for the annually varying uncertainties in climate reconstructions. At the annual scale, fires were synchronized during summers with low precipitation, and most clearly during drought summers. A scale-derivative analysis revealed that fire synchrony and climate varied at similar, roughly decadal scales. Climatic variables and fire synchrony showed varying correlation strength and credibility, depending on the climate variable and the time period. In particular, precipitation emerged as a credible determinant of fire synchrony also at these time scales, despite the large uncertainties in precipitation reconstruction. The findings explain why fire occurrence can be high during cold periods (such as from mid-17th to early 18th century), and stresses the notion that future fire frequency will likely depend to a greater extent on changes in precipitation than temperature alone. We showed, for the first time, the importance of climate as a ...